KORUPSI YANG DILAKUKAN ANGGOTA DPRD DALAM PENDEKATAN HUKUM ISLAM - Dwi Ari Kurniawati (Universitas Islam Malang, 2021)
Based on the description above, the corruption committed by some members of the Regional Representatives Council (DPRD) is no different from corruption by other parties. Means of corruption, including acts violating judicial norms. In Islamic studies, corruption is an act which is forbidden in Islam the legal position is haram. Keharamannya can be searched or arguments based on the teachings of Islam as risywah (bribes), saraqah (theft), al-gasysy (fraud), and khiyanah (betrayal).